2011
DOI: 10.3233/bd-2010-0306
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1/2 mutations and triple negative breast cancers

Abstract: Identifying breast cancer patients at increased risk for carrying a mutation in the BRCA1 and BRCA2 genes is an important objective in clinical practice. Although age at diagnosis, family history of breast and/or ovarian cancer, and ethnicity are all essential parameters to consider when assessing risk, there are limitations as to how well such factors accurately predict BRCA1/2 status, even when quantitative risk models are applied. Integrating information about triple negative (TN) disease may help refine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 45 publications
(55 reference statements)
6
83
1
Order By: Relevance
“…The ratio of TNBC in individuals positive for BRCA1 mutations was 75.8% in this study. According to many reports, the frequency of TNBC in BRCA1 mutation carriers is~60-80% [14]. CIMBA reported the frequency to be 68% [15].…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of TNBC in individuals positive for BRCA1 mutations was 75.8% in this study. According to many reports, the frequency of TNBC in BRCA1 mutation carriers is~60-80% [14]. CIMBA reported the frequency to be 68% [15].…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, family history may be under-reported or uninformative due to paucity of female first degree relatives. In general, the threshold for genetic testing is a mutation probability of ≥20%, and this is currently reached only for cases with a strong family history.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based studies have reported that Black women are approximately two to three times more likely to have triple-negative breast cancer (TNBC) than White women [1, 2] and this clinical subtype of breast cancer has been associated with germline BRCA1 mutations [35]. Even among patients unselected for family history of breast cancer, women with TNBC are more likely to have BRCA1/2 mutations, and these patients are often diagnosed at an earlier age and have higher grade tumors than those without mutations [6].…”
Section: Introductionmentioning
confidence: 99%